Features of indeterminate results of QuantiFERON-TB Gold In-Tube test in patients with haematological malignancies. (July 2021) - Huang, Chen-Cheng; Jerry Teng, Chieh-Lin; Wu, Ming-Feng; Lee, Ching-Hsiao; Chen, Hui-Chen; Huang, Wei-Chang
Background and aims: The application of QuantiFERON-TB Gold in-Tube (QFT-GIT) in patients with haematological malignancies (HMs) has not been well studied. Therefore, we aimed to investigate the features of patients with HMs whose QFT-GIT results were indeterminate. Methods: This study enrolled patients with HMs for the analysis of QFT-GIT tests and additional 2-year follow-up. The characteristics and predictors of QFT-GIT indeterminate results were identified. Mycobacterium tuberculosis (TB) incidence rate (IR) and incidence rate ratio (IRR) were also investigated. Results: Of 89 participants, 27 (30.3%) had QFT-GIT indeterminate results. The QFT-GIT indeterminate patients were characterized with the diagnosis of leukaemia (63.0% versus 32.3%, p = 0.044), abnormal white blood count (WBC) (88.9% versus 14.5%, p = 0.001), abnormal lymphocyte percentage (81.5% versus 14.5%, p = 0.001) and lower lymphocyte count (×10 9 /l) (0.5 versus 2.2, p = 0.000) when compared with those with determinate results. Meanwhile, abnormal WBC [odds ratios (OR): 15.18, p = 0.003] and lymphocyte percentage (OR: 6.90, p = 0.033) were predictors of indeterminate results. One patient with the QFT-GIT indeterminate status and high interferon-γ level of negative control result developed active TB with a TB IR of 18.5 per 1000 person-years and an IRR of 0.1 (95% confidence interval, 0.01–0.71) when compared with positive QFT-GIT patients without prophylaxis treatment. Conclusion: Abnormal ranges of WBC and lymphocyte differential count percentage were independent predictors useful to determine the optimal timing of implementing QFT-GIT test in patients with HMs.